(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article compares the insurance systems of Uzbekistan and foreign countries. Legal foundations, economic factors and practices of insurance systems are studied. The insurance market of Uzbekistan, its development trends, as well as experiences from foreign insurance systems and their importance for the country’s economy are analyzed.